True dermoid cyst in the floor of the mouth - Daniel Antunes Freitas; Jessica Paola Lozano Perez; Luis Carlos Fang Mercado; Antonio José Díaz Caballero (Editorial Ciencias Médicas, 2013)
Dermoid cysts are benign lesions of embryonic origin, with an incidence of 0.01 % of all cysts in the oral cavity. There is no prediction by sex and about 60 % of cases develop at the age of 15 to 35 years old. Knowledge of the clinical findings of such injuries is vital for a definitive diagnosis; however, this should always be confirmed by histopathological examination, especially when making a differential diagnosis between different types of dermoid cyst or other pathologies with similar clinical manifestations. The purpose of this article is to expand knowledge about the diagnosis and treatment of this type of injury because of it is not frequent in the oral cavity. The unusual location of these cysts in the oral cavity makes hard the precise preoperative diagnosis, even with good clinical and radio-graphical assessment. The surgical treatment not only prevents the risk of infectious complications and possible malignancy but also, allows obtaining a definitive diagnosis by a histopathological study. Keywords: dermoid cyst, the floor of the mouth, benign, congenital lesion.